2008
DOI: 10.1002/ep.10291
|View full text |Cite
|
Sign up to set email alerts
|

17α‐Ethinylestradiol: An endocrine disrupter of great concern. Analytical methods and removal processes applied to water purification. A review

Abstract: The xenobiotic 17α‐ethinylestradiol, an oral contraceptive component, is an endocrine disrupter (EDC) of great concern, with fish feminization induced for concentrations as low as ng L−1. EE2 occurrence in the aquatic environment can be linked to insufficient removal in wastewater treatment plants. The focus of this review is to consider optimum treatment processes for removal of EE2. The main problem of EE2 is concentrations often below authors' limits of detection. Consequently, it is important to fully unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 119 publications
1
35
0
4
Order By: Relevance
“…It has been shown that their detection in wastewater adds to the increased antimicrobial resistance, as well as toxicity due to Clarithromycin and Erythromycin. Estradiol is also not fully degraded, and its presence in surface waters [39] affects sea life [41]. As wastewater treatment is suggested to not completely remove the concentrations of these substances in the aquatic environment [14,[16][17][18]39], the solution could be to manage the pollution at the source, which is the human, veterinarian, and agricultural intake and use.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that their detection in wastewater adds to the increased antimicrobial resistance, as well as toxicity due to Clarithromycin and Erythromycin. Estradiol is also not fully degraded, and its presence in surface waters [39] affects sea life [41]. As wastewater treatment is suggested to not completely remove the concentrations of these substances in the aquatic environment [14,[16][17][18]39], the solution could be to manage the pollution at the source, which is the human, veterinarian, and agricultural intake and use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also used as a plasticizer in certain polyvinyl chloride and structural polymers [26]. Because of these ubiquitous uses, a significant chance exists of oral exposure to BPA by organisms [10,[27][28][29]. Despite a wide body of research that reports the deleterious bioactivity of the compound, the actual effect of BPA on the human body is still an area of significant debate.…”
Section: Introductionmentioning
confidence: 98%
“…Due to their incomplete removal during wastewater treatment processes, their widespread presence in the environment, and their endocrine activity even at low concentrations [17,18], these endocrine disruptors have therefore received increased attention in water quality management and health care [19]. However, the monitoring of hormonal active steroids in the environment affecting human health is a major challenge not only for governmental institutions.…”
Section: Introduction: Steroid Hormones Are Of Ecotoxicological Concernmentioning
confidence: 99%